Can Non-Cognitive Skills Programs Improve Achievement? Quasi-Experimental Evidence from EPIS - Pedro S. Martins (Global Labor Organization (GLO), 2017)
Do investments in soft skills pay off in terms of student achievement? This paper evaluates a large private-sector program in this area, EPIS, based on individual and small-group sessions of mediators that seek to improve the non-cognitive skills (e.g. motivation, self-esteem, conscientiousness) of selected students. Our quasi-experimental evidence is drawn from rich longitudinal student data and the different timings of the roll-out of the program, within and across schools. The results highlight the potential of targeted, small-group, non-cognitive interventions, as we find that the EPIS program reduced grade retention by at least 10 percentage points and did so in a cost-effective manner.
Keywords: I20; J08; 330; Student achievement; Non-cognitive skills; Matched School-Student Data